2005
DOI: 10.1554/05-257.1
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Vicariance in Gulf of California Fishes Parallels Vicariant Patterns Found in Baja California Mammals and Reptiles

Abstract: Comparisons across multiple taxa can often clarify the histories of biogeographic regions. In particular, historic barriers to movement should have affected multiple species and, thus, result in a pattern of concordant intraspecific genetic divisions among species. A striking example of such comparative phylogeography is the recent observation that populations of many small mammals and reptiles living on the Baja California peninsula have a large genetic break between northern and southern peninsular populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 80 publications
4
36
0
1
Order By: Relevance
“…Populations of primarily Californian species became isolated in the Gulf following the completion of the formation of the Baja peninsula, or after having invaded the Gulf during glacial periods with lower temperatures. This led to speciation of isolated populations within the Gulf of California (Huang & Bernardi 2001, Bernardi et al 2003a, Riginos 2005, events that contributed to the development of the distinctive fauna of the Cortez Province.…”
Section: Continental Coast Provincesmentioning
confidence: 99%
See 1 more Smart Citation
“…Populations of primarily Californian species became isolated in the Gulf following the completion of the formation of the Baja peninsula, or after having invaded the Gulf during glacial periods with lower temperatures. This led to speciation of isolated populations within the Gulf of California (Huang & Bernardi 2001, Bernardi et al 2003a, Riginos 2005, events that contributed to the development of the distinctive fauna of the Cortez Province.…”
Section: Continental Coast Provincesmentioning
confidence: 99%
“…The gradually expanding set of genetic studies on TEP fishes provides some information. There are indications of speciation occurring very recently within the Gulf of California, due to environmental and habitat differences between the northern and southern sections of the Gulf (Bernardi et al 2003a, Riginos 2005, H. Lin & P. Hastings unpubl. data), and unrelated to major dispersal barriers.…”
Section: Continental Coast Provincesmentioning
confidence: 99%
“…To determine the applicability of this sea level mechanism along coastlines with varying geomorphologies and geologic processes, we perform paleohabitat modelling and genetic assessments of three fish species across widely varying physical settings. We test the ability of our sea level‐based paleohabitat models to explain range‐wide phylogeographic patterns compared to previously hypothesized mechanisms of isolation by distance and seaways (Riginos, ; Stepien, Rosenblatt, & Bargmeyer, ). Finally, we explore the top‐down factors controlling shelf geomorphology to develop a framework that can be used to make and test predictions of sea level change and biotic evolution on other coasts, habitats and species.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have revealed population structure in only some of the species investigated. Furthermore, only the minority of studies have sited barriers with potential to influence H. ingens, while most have attributed population structure to past vicariance only influential to species with more temperate distributions than H. ingens (Bernardi et al 2003;Riginos 2005;Sandoval-Castillo et al 2004), or to ecological barriers (Pfeiler et al 2008) only influential to species with more specialized habitat needs than H. ingens. Thus, the only published barriers with potential to influence H. ingens include geographic distance coupled with low dispersal ability (Craig et al 2006;Riginos and Nachman 2001), and contemporary oceanographic barriers (Bernardi et al 2003;Selkoe et al 2007;Terry et al 2000).…”
Section: Introductionmentioning
confidence: 99%